DEVELOPMENT OF INTEGRATED GAS INSTRUMENTATION SYSTEM IN DIRECT REDUCTION PLANT - A. Adriansyah; F. Rahman (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2016)
Direct reduction is the removal of oxygen from iron without melting process. In direct reduction process, the presence of mixture gas in accordance levels largely determines the performance of the iron produced. Therefore, it needs gas sensors system which has high accuracy and reliability in this process. Unfortunately, there are some things that cause decreasing in the accuracy and reliability of the gas sensor in this process. This paper aims to offer a system that can preserve the accuracy and reliability of the gas measurement system called as Integrated Gas Instrumentation System. The system tends to integrate gas sensor component using Specific Gravity (SG) with other components, such as water trap, filter regulator and monitor gas flow rate. The values of Specific Gravity Meter based on process that display in DCS system are compared with lab results for three type of experiments. Based on experiment results it can be said that the proposed system is able to improve the accuracy and reliability of direct reduction process.